(untitled) (Historia, 2021)
This paper discusses the origin and development of the influence of Dutch, Belgium and German historical thought and traditions on Afrikaans historiography. It accounts for the formative influence of Dutch-German academic education on the first three generations of Afrikaans historians. The influence of Ranke and Huizinga in particular on individual historians and on the education of successive generations established a permanent influence on the practice of history. The pre-war continental view of the study of history as cultural manifestation, was applied at Afrikaans universities until the fifties. But the one-sided interpretation of Afrikaans historiography as dominated by Afrikaner nationalism and apartheid is shown to be in conflict with the real output of Afrikaans historiography. Different approaches were developed by individual Afrikaans historians who interpreted their continental experience of and interest in history in a variety of ways. This continental influence gradually eroded since the 1970’s with the growing influence of the American historical thought in South Africa.